A two‐scale simulation framework for Internal Traverse Grinding. Issue 1 (December 2014) - Holtermann, Raphael; Menzel, Andreas; Schumann, Sebastian; Biermann, Dirk
Abstract We present a hybrid framework which aims at the modelling and simulation of Internal Traverse Grinding of hardened 100Cr6/AISI 52100 by using electro plated cBN grinding wheels. We focus on the thermo‐mechanical loading conditions on the workpiece that results from the interaction of workpiece and tool. The modelling framework basically consists of three components, namely representative plane strain adaptive finite element simulations on a meso‐scale, capturing the proximity of a single cBN grain when cutting through the workpiece bulk. Secondly, we incorporate a kinematic simulation on the process level to gain detailed simulation‐based information on the transient grain‐bulk‐interaction. The third component of the framework consists of a macro‐scale process model that uses the superposed results of the former two components as thermo‐mechanical boundary conditions. Using this framework, we target the prediction of metallurgical effects, such as white layers, on the workpiece on the macro scale in the near future. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)